Community quality-of-life indicators best cases V - Sirgy, M. Joseph; Phillips, Rhonda; Rahtz, D.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
This book contains "best practices" of community quality-of-life indicator systems implemented in various communities throughout the world. The cases in this volume describe communities that have launched their own community indicators programs. Elements that are included in the descriptions are the history of the community indicators work within the target region, the planning of community indicators, the actual indicators that were selected, the data collection process, the reporting of the results, and the use of the indicators to guide community development decisions and public policy.
Preface - Joseph Sirgy, Rhonda Phillips and Don Rahtz.- Author Biographies.- Chapter 1 Comprehensive Local Community Development via Collaborative Quality of Life Planning: Best Practices from Two San Diego Neighborhoods - Mirle Rabinowitz Bussell and Kerry Sheldon.- Chapter 2. Developing and Sustaining a Community Information System for Central Indiana: SAVI as a Case Study - David J. Bodenhamer, James T. Colbert, and Karen Frederickson Comer, and Sharon M. Kandris.- Chapter 3. Twin Cities Compass: Doing Well by Doing Good - Craig Helmstetter, Paul Mattessich, Andi Egbert, Susan Brower, Nancy Hartzler, Jennifer Franklin, and Bryan Lloyd.- Chapter 4. Quality of Life at a Finer Grain: The National Neighborhood Indicators Partnership - G. Thomas Kingsley and Kathryn L.S. Pettit.- Chapter 5. Sustainable Well-being Initiative: Social Divisions and Recovery Process in Minamata, Japan - Takayoshi Kusago.- Chapter 6. The American Human Development Index: Results from Mississippi and Louisiana - Sarah Burd-Sharps, Patrick Guyer, Ted Lechterman, and Kristen Lewis.- Chapter 7. The Metropolitan Philadelphia Indicators Project: Measuring a Diverse Region - Brian Lockwood, Jason Martin, Cathy Yinghui Cao, and Michelle Schmitt.- Chapter 8 Portraits of Peel ? A Community Indicators Portal Project - Srimanta Mohanty.- Chapter 9. The Development of Quality-of-Life Indicators in Rural Areas in Iran: Case Study: Khaveh Shomali District, Lorestan Province - Mohammad Reza Rezvani and Hossain Mansourian.- Chapter 10. Working for Water: A Baseline Study on the Impact of a South African Public Works Programme in Improving the Quality of life of Programme Beneficiaries - Robin Richards.- Chapter 11. Sustainable Urban Development Indicators: The Case of Zadar, a Croatian Coastal Community - Branko I. Cavric.- Chapter 12. Quality of Life in Buffalo City: The Changing Position of African Women in a Post-Apartheid City - Leslie Bank and Ellen Kamman.- Chapter 13. Changes in Living Conditions over Time: A Case Study in South Africa - Valerie Moller and Sarah Radloff.- Chapter 14. Community Indicators in Action: Using Indicators as a Tool for Planning and Evaluating the Health and Wellbeing of a Community - Melanie T. Davern, Sue West, Sally Bodenham, and John Wiseman.
Electronic reproduction.
Keywords: Quality of life; Electronic books